Database of ab initio L-edge X-ray absorption near edge structure - Yiming Chen (Nature Portfolio, 2021)
Measurement(s) near-edge X-ray absorption fine structure spectroscopy • L-edge XANES Technology Type(s) X-ray absorption spectroscopy Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.14233055